Mistargeting of secretory cargo in retromer-deficient cells - Sarah D. Neuman; Erica L. Terry; Jane E. Selegue; Amy T. Cavanagh; Arash Bashirullah (The Company of Biologists, 2021)
Intracellular trafficking is a basic and essential cellular function required for delivery of proteins to the appropriate subcellular destination; this process is especially demanding in professional secretory cells, which synthesize and secrete massive quantities of cargo proteins via regulated exocytosis. The Drosophila larval salivary glands are composed of professional secretory cells that synthesize and secrete mucin proteins at the onset of metamorphosis. Using the larval salivary glands as a model system, we have identified a role for the highly conserved retromer complex in trafficking of secretory granule membrane proteins. We demonstrate that retromer-dependent trafficking via endosomal tubules is induced at the onset of secretory granule biogenesis, and that recycling via endosomal tubules is required for delivery of essential secretory granule membrane proteins to nascent granules. Without retromer function, nascent granules do not contain the proper membrane proteins; as a result, cargo from these defective granules is mistargeted to Rab7-positive endosomes, where it progressively accumulates to generate dramatically enlarged endosomes. Retromer complex dysfunction is strongly associated with neurodegenerative diseases, including Alzheimer's disease, characterized by accumulation of amyloid β (Aβ). We show that ectopically expressed amyloid precursor protein (APP) undergoes regulated exocytosis in salivary glands and accumulates within enlarged endosomes in retromer-deficient cells. These results highlight recycling of secretory granule membrane proteins as a critical step during secretory granule maturation and provide new insights into our understanding of retromer complex function in secretory cells. These findings also suggest that missorting of secretory cargo, including APP, may contribute to the progressive nature of neurodegenerative disease.